El Toro 1936-11 (November 1936) - San Jose State College:::Creator::::::::::::; Spangler, Jewel:::Editor::::::::::::
Founded in 1935 by Jordan Kellogg, El Toro was a college humor magazine featuring short jokes, cartoons, and articles of a satirical or humorous nature.